Regulation of the subcellular trafficking of CD36, a major determinant of cardiac fatty acid utilization. - Glatz, J; Nabben, M; Heather, L; Bonen, A; Luiken, J (Elsevier, 2016)
Myocardial uptake of long-chain fatty acids largely occurs by facilitated diffusion, involving primarily the membrane-associated protein CD36. Other putative fatty acid transporters, such as FABPpm, FATP1 and FATP4, also play a role, but their quantitative contribution is much smaller or their involvement is rather permissive. Besides its sarcolemmal localization, CD36 is also present in intracellular compartments (endosomes). CD36 cycles between both pools via vesicle-mediated trafficking, and the relative distribution between endosomes versus sarcolemma determines the rate of cardiac fatty acid uptake. A net translocation of CD36 to the sarcolemma is induced by various stimuli, in particular hormones like insulin and myocyte contractions, so as to allow a proper coordination of the rate of fatty acid uptake with rapid fluctuations in myocardial energy needs. Furthermore, changes in cardiac fatty acid utilization that occur in both acute and chronic cardiac disease appear to be accompanied by concomitant changes in the sarcolemmal presence of CD36. Studies in various animal and cell models suggest that interventions aimed at modulating the sarcolemmal presence or functioning of CD36 hold promise as therapy to rectify aberrant rates of fatty acid uptake in order to fight cardiac metabolic remodeling and restore proper contractile function. In this review we discuss our current knowledge about the role of CD36 in cardiac fatty acid uptake and metabolism in health and disease with focus on the regulation of the subcellular trafficking of CD36 and its selective modulation as therapeutic approach for cardiac disease.